Minat bahasa siswa SD/MI dan penerapan dalam kehidupan sehari hari - Mubarokah, Siti (Maliki Interdisciplinary Journal, 2023)
Children are the key to the success of a country in the future. Educating them is not only an obligation for educated personnel but also for all of us to produce a generation that is insightful and represents national identity. Especially, in the language that is "Indonesian". Where as we know there are still many who use their mother tongue/region. That’s why I wrote this article so that the next generation really knows the meaning and use of good and correct language in everyday life.